Training programme effectiveness from the operational employee’s perspectives: A comparative study between the selected local and foreign banks of Dubai, UAE - Bose, Indranil; Gupta, Vishwas; Mudgal, Rakesh Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Training needs are being regularly assessed for the operational level employees across banking sector in UAE. These banks have sufficiently large number of employees, who are employed at the branch level and engaged in daily banking operations like transactions across teller counters, processing papers on credit application, selling financial products like mutual funds and insurances etc. Performance of these large numbers of employees plays a very critical role in setting the direction of not only the respective branch performance, but also of the overall organization as a whole. Therefore, regular training is required for the continuous improvement in the performance of this category of workforce and both local and foreign banks design and develop the training programmes according to their respective priorities. Based on the feedback of 498 operational employees of 16 branches of four major banks, two each from local and foreign bank categories, located in emirates of Dubai, the present study attempts to analyse the major determinants of the training need assessment and the level of different types benefits from such training interventions as perceived by the respondents.